Electrochemical Determination and Removal of Pentachlorophenol at Diamond Electrodes - Codognoto,L. (2005)
This work describes the determination of pentachlorophenol (PCP) in pure and polluted waters by square wave voltammetry (SWV) and the influence of the electrode potential on PCP oxidation on boron doped diamond (BDD) electrodes. Measurements carried out in solutions of the Britton-Robinson buffer with pH = 5.5 revealed a single oxidation peak at 0.80 V vs. Ag/AgCl for PCP in a process that is controlled by the adsorption of the species. The detection limits obtained were 5.5 mg L-1 in pure water and 15.5 mg L-1 for water taken from a local creek, respectively. Controlled potential electrolyses were carried at 0.9, 2.0 and 3.0 V vs. Ag/AgCl and the solutions analysed by SWV, HPLC, chloride ion selective electrode and UV-vis spectroscopy. At low positive potential (0.9 V), the formation of an adherent film on the electrode surface involving the transference of 1 electron per PCP molecule was observed. At potentials close to the onset of O2 evolution (2.0 V), the formation of the corresponding quinone was detected. Electrolyses carried out well into the region of oxygen evolution (3.0 V) lead to the total combustion of PCP to CO2 and H2O as well as to the release into solution of 5 Cl- ions per PCP molecule destroyed.